2016
DOI: 10.3319/tao.2016.01.06.01(tem)
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Shallow Soil Response Using Wave Propagation Numerical Modelling in the Western Plain of Taiwan

Abstract: This study used the results from 45 microtremor array measurements to construct a shallow shear wave velocity structure in the western plain of Taiwan. We constructed a complete 3D velocity model based on shallow and tomography models for our numerical simulation. There are three major subsurfaces, engineering bedrock (V S = 600 m s -1 ), Pliocene formation and Miocene formation, constituted in the shallow model. The constant velocity is given in each subsurface. We employed a 3D-FD (finite-differences) method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The shallow velocity structure of the Chianan plain was investigated using the microtremor array analysis (Kuo et al 2016a). The soil response was simulated (Chen et al 2016) by considering the shallow structure, and the results revealed that the shallow soft layers influenced the duration of seismic wave shaking and ground motion amplification in the Tainan area. Darragh and Shakal (1991) analyzed spectral ratios for two rock and soil station pairs and estimated the site response from weak and strong ground motions.…”
Section: Introductionmentioning
confidence: 99%
“…The shallow velocity structure of the Chianan plain was investigated using the microtremor array analysis (Kuo et al 2016a). The soil response was simulated (Chen et al 2016) by considering the shallow structure, and the results revealed that the shallow soft layers influenced the duration of seismic wave shaking and ground motion amplification in the Tainan area. Darragh and Shakal (1991) analyzed spectral ratios for two rock and soil station pairs and estimated the site response from weak and strong ground motions.…”
Section: Introductionmentioning
confidence: 99%